Republic of Yemen : 2008 Article IV Consultation; Staff Report; Staff Statement and Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Yemen. (IMF Staff Country Reports; Country Report, 2009)
Recent economic performance in Yemen has been mixed. A sharp decline in oil production, coupled with inflexible government expenditure and only marginal improvement in the tax-to-GDP ratio led to an overall fiscal deficit of 5.8 percent in 2007. Executive Directors have noted that Yemen's non-oil GDP growth has been solid in recent years, and progress has been made on a number of structural reforms. Directors have welcomed the authorities' commitment to reduce expenditure in the event that oil prices remain below the benchmark price in the 2009 budget.